Inhabiting the Return through Memory and Writing - Garzón, María Angélica (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The present article uses literary writing with the aim of exposing the ways in which three “returning” populations in the region of Montes de María resignify the places from which they were forcefully expelled, making them habitable again through practices of memory. The starting point for this researchn is the idea that the “return” of a population is a process in itself and not the final chapter of forced displacement. For this purpose I rely on ethnographic work and the compilation of testimonies aided by creative writing and poetical anthropology- in order to propose an expositive, sensitive form of writing that will allow me to examine the process of return of this population, from a subjective position. As a conclusion, I propose the dialogue between anthropology and creative writing as a powerful tool to in vestigate different processes of reconstruction engaged in by persons affected by the Colombian armed conflict.